2014
DOI: 10.3390/ijms16010193
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Its Significant Roles in Neurodegenerative Diseases and Cancer

Abstract: Reactive oxygen and nitrogen species have been implicated in diverse pathophysiological conditions, including inflammation, neurodegenerative diseases and cancer. Accumulating evidence indicates that oxidative damage to biomolecules including lipids, proteins and DNA, contributes to these diseases. Previous studies suggest roles of lipid peroxidation and oxysterols in the development of neurodegenerative diseases and inflammation-related cancer. Our recent studies identifying and characterizing carbonylated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
240
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 363 publications
(271 citation statements)
references
References 141 publications
0
240
0
3
Order By: Relevance
“…This presents a major challenge to genomic stability (3)(4)(5)(6) and is implicated in the pathogenesis of multiple human diseases, including cancer and neurodegenerative disorders (7,8). Abundant DNA damage from oxidative stress constitutes ∼10% of all DNA lesions and includes oxidative DNA damage, such as base damage, sugar moiety damage, apurinic/apyrimidinic (AP) sites, DNA single-strand breaks (SSBs), and double-strand breaks (DSBs) (2,6).…”
mentioning
confidence: 99%
“…This presents a major challenge to genomic stability (3)(4)(5)(6) and is implicated in the pathogenesis of multiple human diseases, including cancer and neurodegenerative disorders (7,8). Abundant DNA damage from oxidative stress constitutes ∼10% of all DNA lesions and includes oxidative DNA damage, such as base damage, sugar moiety damage, apurinic/apyrimidinic (AP) sites, DNA single-strand breaks (SSBs), and double-strand breaks (DSBs) (2,6).…”
mentioning
confidence: 99%
“…In the area of cancer, antioxidants are increasing in importance. Indeed, it has been reported that antioxidants can prevent cancer due to their effects on oxidative stress [17].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress have been found not only in brain tissues but also in peripheral tissues of individuals affected by PD, mild cognitive impairment (MCI) and other degenerative diseases, including HD, Alzheimer's disease (AD), amyotrophic lateral sclerosis (ALS), and others [222]. Therefore, a delicate balance between the levels of oxidants and antioxidants is essential to maintain the optimum levels of ROS [229].…”
Section: Oxidative Stress and Pdmentioning
confidence: 99%